Racial disparities in end-stage renal disease in a high-risk population: the Southern Community Cohort Study - Bock, Fabian (BMC Nephrol, 2019)
INTRODUCTION: The Southern Community Cohort Study is a prospective study of low socioeconomic status (SES) blacks and whites from the southeastern US, where the burden of end-stage renal disease (ESRD) and its risk factors are high. We tested whether the 2.4-fold elevated risk of ESRD we previously observed in blacks compared to whites was explained by differences in baseline kidney function. METHODS: We conducted a case-cohort study of incident ESRD cases (n = 737) with stored blood and a probability sampled subcohort (n = 4238) and calculated estimated glomerular filtration rate (eGFR) from serum creatinine. 86% of participants were enrolled from community health centers in medically underserved areas and 14% from the general population in 12 states in the southeastern United States. Incident ESRD after entry into the cohort was ascertained by linkage of the cohort with the US Renal Data System (USRDS). RESULTS: Median (25th, 75th percentile) eGFR at baseline was 63.3 (36.0, 98.2) ml/min/1.73m(2) for ESRD cases and 103.2 (86.0, 117.9) for subcohort. Black ESRD cases had higher median (25th, 75th) eGFR [63.3 (35.9, 95.9)] compared to whites [59.1 (39.4, 99.2)]. In multivariable Cox models accounting for sampling weights, baseline eGFR was a strong predictor of ESRD risk, and an interaction with race was detected (P = 0.029). The higher ESRD risk among blacks relative to whites persisted (hazard ratio: 2.58; 95% confidence interval: 1.65, 4.03) after adjustment for eGFR. CONCLUSION: In this predominantly lower SES cohort, the racial disparity in ESRD risk is not explained by differences in baseline kidney function. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12882-019-1502-z) contains supplementary material, which is available to authorized users.